2016
DOI: 10.18203/issn.2454-5929.ijohns20160062
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology, diagnosis and treatment of chronic rhinosinusitis: a study in a teaching hospital in Telangana

Abstract: <p class="abstract"><strong>Background:</strong> Chronic rhinosinusitis is one of the common problems in ENT Department which can be caused due to infections or anatomical blockage or allergy. We performed this study to assess the cause, clinical features and the effect of treatment on rhinosinusitis.</p><p class="abstract"><strong>Methods:</strong> 60 patients of chronic sinusitis with symptoms persisting beyond three months, Nasal Endoscopic findings with Polyps/Disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
3
2
0
Order By: Relevance
“…Among 80 patients enrolled in our study, 65% were male and 35% were female. Similar results were reported in a study by Surapaneni et al (18). All 80 patients in our study had more than one cardinal symptom (Table 2).…”
Section: Discussionsupporting
confidence: 93%
“…Among 80 patients enrolled in our study, 65% were male and 35% were female. Similar results were reported in a study by Surapaneni et al (18). All 80 patients in our study had more than one cardinal symptom (Table 2).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, males were more commonly affected with chronic rhinosinusitis accounting for 58% and females accounted for 42%. This is similar to the study conducted by Surapaneni H et al 20 which had reported the incidence of male candidates affected to be 60% and females 40%. Most of the previous studies performed by vinodhini P 21 , Dua et al 22 , Iseh et al 23 , Gibelli D et al 1 , had showed male preponderance with 66%, 57.5%, 52% and 63% respectively.…”
Section: Discussionsupporting
confidence: 91%
“…7 In our study, we have observed about 31% of the total cases affected with chronic rhinosinusitis were in the age range of 20-30 years. Surapaneni H et al 20 in the year 2016 conducted a study to determine the underlying cause, clinical features and the impact of treatment on chronic rhinosinusitis patients and had observed that 41.7% of patients with chronic rhinosinusitis fell in the age group 16 -30 yrs similar to our study. Another study conducted by Gibelli D 1 et al reported that the affected age group of chronic rhinosinusitis were in the age range of 21 -40 years accounting for 65.3% of their study population.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is also closely related to asthma as 10-40% of people with rhinitis have concomitant asthma, According to WHO, the prevalence of allergic rhinitis ranges between 10% to 32% in Asia, very similar to our study. 11 Chronic rhinosinusitis is one the common problems encountered in ENT department. It does not affect a particular age or sex and is more common among patients with an upper respiratory tract infection.…”
Section: Discussionmentioning
confidence: 99%